Protocol of DREAM3R: DuRvalumab with chEmotherapy as first-line treAtment in advanced pleural Mesothelioma—a phase 3 randomised trial. Issue 1 (25th January 2022) - Kok, Peey Sei; Forde, Patrick M; Hughes, Brett; Sun, Zhuoxin; Brown, Chris; Ramalingam, Suresh; Cook, Alistair; Lesterhuis, Willem Joost; Yip, Sonia; O'Byrne, Ken; Pavlakis, Nick; Brahmer, Julie; et al.
Abstract : Introduction: There is a strong theoretical rationale for combining checkpoint blockade with cytotoxic chemotherapy in pleural mesothelioma and other cancers. Two recent single-arm, phase 2 trials [DuRvalumab with chEmotherapy as first-line treAtment in advanced pleural Mesothelioma (DREAM) and Phase II multicenter study of anti-PD-L1, durvalumab, in combination with cisplatin and pemetrexed for the first-line treatment of unresectable malignant pleural mesothelioma (PrE0505)] combining the programmed death ligand-1 (PD-L1) inhibitor durvalumab with standard first-line chemotherapy exceeded prespecified safety and activity criteria to proceed to a phase 3 confirmatory trial to assess this combination. We present the protocol of the DREAM3R trial. Methods and analysis: This multicentre open-label randomised trial will recruit 480 treatment-naïve adults with advanced pleural mesothelioma, randomised (2:1) to either 3-weekly durvalumab 1500 mg plus 3-weekly doublet chemotherapy (cisplatin 75 mg/m 2 or carboplatin, Area Under the Curve, AUC 5 and pemetrexed 500 mg/m 2 ) 4–6 cycles, followed by 4-weekly durvalumab 1500 mg until disease progression, unacceptable toxicity or patient withdrawal; OR doublet chemotherapy alone for 4–6 cycles, followed by observation. The target accrual time is 27 months, with follow-up for an additional 24 months. This provides over 85% power if the true HR for overall survival (OS) is 0.70, with two-sided alpha of 0.05, assuming a median OS of 15 months in the control group. Randomisation is stratified by age (18–70 years vs >70), sex, histology (epithelioid vs non-epithelioid), platinum agent (cisplatin vs carboplatin) and region (USA vs Australia/New Zealand vs Other). The primary endpoint is OS. Secondary endpoints include progression-free survival, objective tumour response (by mRECIST V.1.1 and iRECIST), adverse events, health-related quality of life and healthcare resource use. Tertiary correlative objectives are to explore and validate potential prognostic and/or predictive biomarkers (including features identified in the DuRvalumab with chEmotherapy as first-line treAtment in advanced pleural Mesothelioma (DREAM) and PrE0505 studies, PD-L1 expression, tumour mutational burden, genomic characteristics and human leukocyte antigen subtypes) in tissue and serial blood samples. An imaging databank will be assembled for validation of radiological measures of response, and studies of possible radiomic biomarkers in mesothelioma. Ethics and dissemination: The protocol was approved by human research ethics review committees for all participating sites. Results will be disseminated in peer-reviewed journals and at scientific conferences. Drug Supply: AstraZeneca. Protocol version: CTC 0231 / TOGA 18/001 / PrE0506 3.0, 29 July 2021. Trial registration number: ClinicalTrials.gov Identifier: NCT04334759 ACTRN 12620001199909.